2012
DOI: 10.1073/pnas.1121624109
|View full text |Cite
|
Sign up to set email alerts
|

Floral humidity as a reliable sensory cue for profitability assessment by nectar-foraging hawkmoths

Abstract: Most research on plant-pollinator communication has focused on sensory and behavioral responses to relatively static cues. Floral rewards such as nectar, however, are dynamic, and foraging animals will increase their energetic profit if they can make use of floral cues that more accurately indicate nectar availability. Here we document such a cue-transient humidity gradients-using the night blooming flowers of Oenothera cespitosa (Onagraceae). The headspace of newly opened flowers reaches levels of about 4% ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 65 publications
(54 reference statements)
11
148
1
Order By: Relevance
“…It has been shown that plumes emitted by flowers contain increased humidity [25] and CO 2 [26] and that both cues can be used by moths to pinpoint the flower. However, this information appears to be relevant only in specific context since behavioral responses to D. wrightii flowers can be mimicked by widely reduced synthetic blends devoid of humidity or CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that plumes emitted by flowers contain increased humidity [25] and CO 2 [26] and that both cues can be used by moths to pinpoint the flower. However, this information appears to be relevant only in specific context since behavioral responses to D. wrightii flowers can be mimicked by widely reduced synthetic blends devoid of humidity or CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Floral warmth may act as a cue for pollinators (signalling improved nectar rewards) as well as a reward [39]. Other cues recently shown to be used by hawkmoths are CO 2 [40,41] and relative humidity [42]: like floral warmth, these will be effective only under certain environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental flows could affect moths in other ways. Moths use visual and olfactory clues to discern between flowers of different nectar content (Raguso and Willis, 2005;von Arx et al, 2012), and this capability can also be influenced by airflow turbulence. Field observations are required to determine the importance of these factors to wild moths and in general for nectar feeders.…”
Section: Ecologymentioning
confidence: 99%